Can groundwater be protected from the pressure of china's urban growth?. (October 2020) - Hua, Shanshan; Jing, Hao; Yao, Yingying; Guo, Zhilin; Lerner, David N.; Andrews, Charles B.; Zheng, Chunmiao
Abstract: Groundwater is expected to be more vulnerable to water-quality degradation in the future due to rapid urbanization. However, despite knowledge that protecting future groundwater resources is necessary for sustainable groundwater resource development, little is known about the role of groundwater policy in influencing the spatial distribution of urbanization. This study sheds light on how a policy that protects vulnerable groundwater could affect the distribution of urban expansion. Groundwater vulnerability to pollution under future climate change scenarios is used as a factor to generate urban expansion probability maps for China. The results indicate that there will be a significant and uneven urban growth by 2030, if current trends in urban expansion continue. The amount of urban land in 2030 will range from 2.9 to 4.2 times the urban area in 2010. Meanwhile, the urban expansion probability maps for projections with and without consideration of groundwater vulnerability in urban suitability are compared. The comparation shows that consideration of a groundwater policy would significantly alter the future spatial distribution of urban areas. Even with a weight of only 10% for groundwater vulnerability in the urban suitability consideration, the percentage of change area in the urban expansion probability distribution map can be as high as 60%. The probabilities of urban expansion are forecast to gradually transfer from the southeast coastal areas to inland areas as higher weight (from 10% to 50%) of groundwater vulnerability is given to urban suitability consideration. Our study demonstrates that groundwater protection from urbanization pressures can be achieved, provides support for policy and decision makers in evaluating options to modify existing urban expansion policies, and concludes that groundwater protection at the macro-scale is an appropriate policy goal.